So Much Change! - Shaunda French-Collins; James F. Koehn; Wendy Waugh (Academic Chairpersons Conference Proceedings, 2023)
Presenters will examine change and change management in higher education leadership. For example, creating and managing fully remote faculty. Additionally, presenters will examine the importance of flexibility, as roles and demands change within administration. Lastly, participants will discuss strategies for navigating change.
Keywords: Change Management; Remote Faculty; Academic Leadership; Career Flexibility